INFLUENCE OF DIETARY PATTERN ON HEART RATE VARIABILITY IN MENOPAUSE SYNDROME - A SANGEETHA,; R ARCHANA, (International Journal of Pharma and Bio Sciences, 2016)
Epidemiological studies have shown an increased incidence of cardiovascular disease in postmenopausal women compared to age-matched men and premenopausal women because of disturbed activity of cardiac autonomic functions. Improving the diet, by consuming more of fruits and green leafy vegetables is an important strategy to reduce the risk of cardiovascular disease. Measurement of heart rate variability (HRV) is the easiest tool to detect cardiovascular disease. In this study we have assessed the influence of dietary pattern on menopause syndrome by assessing the heart rate variability and grading the menopausal symptoms. HRV was studied by recording the ECG in digital physiograph. Changes in menopausal symptoms were measured using a validated Greene Climacteric Scale. A total of 57 healthy postmenopausal women aged from 45 – 65 years have participated in the study. Heart rate variability frequency domain method showed increased vagal activity among vegetarian women. They exhibited significantly lower menopausal symptom scores compared to the non-vegetarian group. Vegetarian food is a natural and effective approach to reduce the severity of menopausal symptoms and risk of cardiovascular disease in post menopausal women.